Investigation of the potential of sustainable cork composites for structures under impact - Ferreira, João Bernardo dos Santos Soveral (2022)
Cork has been used since the dawn of humanity, when it was used in fishing instruments, floats, shoes, etc. Currently, this material has been targeted to protective equipment, because it presents a good energy absorption capacity in impact situations. In order to improve this equipment, new cork and polyurethane composites will be studied with the help of numerical modeling, evaluating their physical characteristics and energy absorption capacity in impact situations. Being recyclable and natural, cork presents an excellent solution to the problem of environmental sustainability. In this work, numerical tests will be performed on cork composites using Abaqus. In the first stage of the work, single impact tests were performed in order to validate the constitutive strategy, by comparing the simulation results with the experimental tests, and validating numerically all the samples provided. In the second part, the application of these composites in structures such as helmets was evaluated, concluding that two of the evaluated materials could be used in low energies’ impacts.